2019
DOI: 10.1155/2019/2923549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Multidrug-Resistant Tuberculosis (MDR-TB) among Presumptive MDR-TB Patients in Tigray Region, Northern Ethiopia

Abstract: Background. Tuberculosis (TB) is one of the major public health problems. There are alarming reports of increasing multidrug-resistant tuberculosis (MTR-TB) from various parts of the globe, including Ethiopia. This study was designed to determine the prevalence and factors associated with MDR-TB among presumptive MDR-TB cases in Tigray Regional State, Ethiopia. Methods. A cross-sectional study was conducted in Tigray Regional State from 2015 to 2016. Two hundred sputum samples were collected, transported, proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 23 publications
7
26
5
Order By: Relevance
“…The prevalence of MDR-TB in our study was 1.1% somewhat minimal compared with the National MDR-TB prevalence [ 3 ]. However, our result was in line with previous studies in our country [ 8 , 9 , 30 , 31 ]. High MDR-TB (4.3%) prevalence was reported from the National Tuberculosis Reference Laboratory and the seven Regional Laboratories among newly diagnosed TB patients [ 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of MDR-TB in our study was 1.1% somewhat minimal compared with the National MDR-TB prevalence [ 3 ]. However, our result was in line with previous studies in our country [ 8 , 9 , 30 , 31 ]. High MDR-TB (4.3%) prevalence was reported from the National Tuberculosis Reference Laboratory and the seven Regional Laboratories among newly diagnosed TB patients [ 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…(6/95) and INH 2.1% (2/95) mono-resistance, the current prevalence in line with a number of studies [18,29,30] that rifampicin mono-resistant is greater than isoniazid mono-resistant with varying degrees of proportion. Such RIF resistance is an important implication for higher risk of multi-drug resistance as it is a surrogate marker of MDR [28].…”
Section: Socio-demographic Characteristics Genotypic and Phenotypic supporting
confidence: 80%
“…In the current study, none of the sociodemographic factors were statistically associated with MDR-TB development, which is similar with other study reports [ 24 , 58 , 63 ]. A recent similar study in the Tigray Region reported that age was marginally associated with MDR-TB [ 64 ]. Yet, this result could not be reproduced in our study.…”
Section: Discussionmentioning
confidence: 99%